Nagaoka Japan's Forgotten Capital - Van Goethem, Ellen (Brill's Japanese Studies Library, 2008)
This comprehensive account of the Nagaoka capital discusses the capital's construction and layout, and investigates the motivations behind the establishment and abrupt abandonment of Nagaoka within the context of Kanmu's reign and personal convictions. ; Readership: All those interested in ancient Japanese history and archaeology, in particular the rule of the late eighth-century sovereign Kanmu, capital building and relocation, political intrigue, and mokkan (inscribed wooden tablets).